Improved Small Object Detection for Road Driving based on YOLO-R - Huang, Yu-Fang; Liu, Tsung-Jung; Liu, Kuan-Hsien (IEEE International Conference on Consumer Electronics-China (Online), 2022)
With the popularization of self-driving cars, more and more researches have been done on road object detection. However, many challenges remain to be resolved, such as the detection accuracy of small objects in the long distance. Therefore, we propose an algorithm based on YOLO-R to improve the detection accuracy to deal with the actual situation in this field. First, we set some conditions and propose some methods to balance the problem of extremely unbalanced size among each target label. Secondly, the Mish activation function is selected for training. Finally, we use the stochastic gradient descent (SGD) method to ensure that the best global solution can be obtained, and experiments on the BDD100k dataset show that our method has better results than other models in this dataset.